A novel modified penile disassembly procedure for isolated male epispadias repair: preliminary outcomes - Deng, Fuming; Fu, Wen; Liu, Guochang; Sun, Liangzhong (Frontiers in Pediatrics, 2024)
Purpose This study aimed to evaluate the preliminary outcome of a novel modification of a penile disassembly procedure. Methods We retrospectively reviewed the data of 15 patients with isolated male epispadias (IME) who underwent a modified penile disassembly procedure. This modification involved leaving the glans connected while dissecting the urethral plate from the corpus cavernosum. This approach reserves the bundles of the anastomosis at the glans, which can prevent ischemic changes. Results One of the first two patients experienced glans ischemic changes on the first day after the operation, which ultimately resulted in the loss of half of the hemiglans. Urethral plate shortening was observed in two patients and was addressed with a transverse preputial island flap. Two patients developed a penopubic urethral fistula, which was repaired 6 months postoperatively. Of the 15 patients, 10 (66%) were continent or social continent, while 4 were incontinent and needed bladder neck reconstruction. One patient had not yet reached the age for continence evaluation. Additionally, Two patients had a residual dorsal curvature of approximately 10–15° and were advised to undergo continuous follow-up. Conclusions The modified penile disassembly procedure is a simple, effective, and safe method for IME repair with an acceptable penile appearance and complication rate.